2022
DOI: 10.1111/1751-7915.14164
|View full text |Cite
|
Sign up to set email alerts
|

The host niches of soybean rather than genetic modification or glyphosate application drive the assembly of root‐associated microbial communities

Abstract: Plant roots significantly influence soil microbial diversity, and soil microorganisms play significant roles in both natural and agricultural ecosystems.Although the genetically modified (GM) crops with enhanced insect and herbicide resistance are thought to have unmatched yield and stress resistance advantages, thorough and in-depth case studies still need to be carried out in a real-world setting due to the potential effects of GM plants on soil microbial communities. In this study, three treatments were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Understanding the mechanisms by which bacteria colonize the root‐associated niches is crucial for processes related to the application of the beneficial bacteria, including the screening of strains with efficient root colonization ability and directed strain improvement (Yang et al, 2022 ). By characterizing the colonization abilities of single gene deletion mutants or high‐throughput transposon mutagenesis libraries of the beneficial strains after being inoculated into the sterilized plants, or profiling the transcriptome of strains stimulated by root exudates, recent studies have identified several genes involved in bacterial root colonization, such as those involved in the biosynthesis of chemotaxis system, flagella, and lipopolysaccharides (LPS) (Cole et al, 2017 ; Coutinho et al, 2015 ; Feng et al, 2021 ; Ishizawa et al, 2022 ; Knights et al, 2021 ; Wallner et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms by which bacteria colonize the root‐associated niches is crucial for processes related to the application of the beneficial bacteria, including the screening of strains with efficient root colonization ability and directed strain improvement (Yang et al, 2022 ). By characterizing the colonization abilities of single gene deletion mutants or high‐throughput transposon mutagenesis libraries of the beneficial strains after being inoculated into the sterilized plants, or profiling the transcriptome of strains stimulated by root exudates, recent studies have identified several genes involved in bacterial root colonization, such as those involved in the biosynthesis of chemotaxis system, flagella, and lipopolysaccharides (LPS) (Cole et al, 2017 ; Coutinho et al, 2015 ; Feng et al, 2021 ; Ishizawa et al, 2022 ; Knights et al, 2021 ; Wallner et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%